The Study of Paper Capillarity with a Simple Technique - Septia Ardiani; Handika Rahmayanti; Nurul Akmalia (Jurnal Ilmiah Publipreneur, 2020)
The study of water absorption by capillarity on paper with a simple technique is simple but important to do to inform the public about the characteristics of paper and for the development of research on the absorption of different types of paper. In this study, five types of paper were used, namely HVS paper, cardboard, tissue paper, concord paper and buffalo paper. In the capillary water absorption test on paper, the physical quantities analyzed are the water absorption, the absorption time and the water absorption rate. The capillarity of the paper is a comparison of the rate of water absorption by the paper which is analyzed using the straight line movement approach. The value of water absorption is estimated using the ratio between the height of water absorption and the time absorption. Based on the results of the capillary test on paper, it was found that the water absorption height for the five types of paper increases with increasing absorption time. The highest water absorption capacity is tissue paper, which is 7.4 Â± 0.2 cm every 180 seconds. While the lowest water absorption capillarity is HVS paper which is 0.5 Â± 0.1 cm at the 180th second. Cardstock and buffalo paper have almost the same water absorption value and are higher than HVS paper and match. The absorption speed which is almost the same between cardboard and buffalo paper is due to the fact that both belong to the same type of paper, namely printing paper.Â